The post-vaccine microevolution of invasive Streptococcus pneumoniae - Cremers, A.J.H.; Mobegi, Fredrick; De Jonge, M.I.; Van Hijum, S.A.F.T.; Meis, J.F.; Hermans, P.W.M.; Ferwerda, G.; Bentley, S.D.; Zomer, A.L. (NATURE PUBLISHING GROUP, 2015)
The 7-valent pneumococcal conjugated vaccine (PCV7) has affected the genetic population of Streptococcus pneumoniae in pediatric carriage. Little is known however about pneumococcal population genomics in adult invasive pneumococcal disease (IPD) under vaccine pressure. We sequenced and serotyped 349 strains of S. pneumoniae isolated from IPD patients in Nijmegen between 2001 and 2011. Introduction of PCV7 in the Dutch National Immunization Program in 2006 preluded substantial alterations in the IPD population structure caused by serotype replacement. No evidence could be found for vaccine induced capsular switches. We observed that after a temporary bottleneck in gene diversity after the introduction of PCV7, the accessory gene pool re-expanded mainly by genes already circulating pre-PCV7. In the post-vaccine genomic population a number of genes changed frequency, certain genes became overrepresented in vaccine serotypes, while others shifted towards non-vaccine serotypes. Whether these dynamics in the invasive pneumococcal population have truly contributed to invasiveness and manifestations of disease remains to be further elucidated. We suggest the use of whole genome sequencing for surveillance of pneumococcal population dynamics that could give a prospect on the course of disease, facilitating effective prevention and management of IPD.